Salmonella exploits LRRK2-dependent plasma membrane dynamics to invade host cells - Hongxian Zhu; Andrew M. Sydor; Bing-Ru Yan; Ren Li; Michal T. Boniecki; Carina Lyons; Miroslaw Cygler; Aleixo M. Muise; Michelle E. Maxson; Sergio Grinstein; Brian Raught; John H. Brumell (Nature Communications)
Abstract Salmonella utilizes type 3 secreted effector proteins to induce plasma membrane (PM) perturbations during invasion of host cells1. The effectors drive mobilization of host membranes to generate cell surface ruffles, followed by invagination and scission of the PM to generate Salmonella-containing vacuoles (SCVs)2. Here, we show that LRRK2 kinase generates membrane reservoirs exploited by Salmonella during invasion. The reservoirs are tubular compartments associated with the PM under basal conditions and are formed through the phosphorylation of RAB10 GTPase by LRRK2. Mobilization of membrane reservoirs to generate invasion ruffles mediates delivery of phosphorylated RAB10 to invasion sites. Subsequently, RAB10 dephosphorylation is required for its inactivation by a bacterial GTPase activating protein and subsequent scission of the PM. RAB10 dephosphorylation is mediated by a TLR4/PIEZO1/TMEM16F-dependent pathway and is inhibited by hyperactive variants of LRRK2. Our findings reveal how Salmonella exploits LRRK2-dependent PM dynamics during invasion and provide new insight into how LRRK2 variants can protect against bacterial infection3,4.